A review study on corporate fraud's negative effects on corporations / Muhammad Aiman Awalluddin, Anisa Safiah Maznorbalia and Mohamad Suhairi Yiam - Awalluddin, Muhammad Aiman; Maznorbalia, Anisa Safiah; Yiam, Mohamad Suhairi (2022)
The economic repercussions of corporate fraud are significant and widespread. The seemingly unstoppable misbehavior of corporate managers harms shareholders, stakeholders, and the financial system. Corporate fraud is defined as illegal, unethical, and deceptive actions committed by a company or an individual acting in their capacity as an employee of the company. It harms the company's reputation and is capable of causing direct financial loss. It could make it harder to attract and retain business partners, customers, and employees. It could lead to a breach of banking covenants or expose the company to regulatory costs, legal fines, and sanctions, which could jeopardize its ability to maintain a competitive advantage. The purpose of this article is to explore the negative effects of corporate fraud by using basic literature review methods to search, critically appraise, and synthesize the studied issue. It summarizes the evidence on the researched topic by synthesizing the findings of multiple primary studies on the negative impact of corporate fraud. In developing the discussion themes, a case study on the previous fraud scandal was analyzed to explore corporate fraud's most common and threatening implications. Regarding the effects of fraud, this topic is important for the management of financial institutions, accountants, auditors, and everyone else involved.